2005
DOI: 10.1177/0095399704272594
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Matters

Abstract: An important feature of the new public management paradigm is the increasing reliance on voluntary codes rather than coercive mandatory regulation to achieve public policy objectives. Often, the proponents of new public management overlook the important contributions of policy entrepreneurs within regulated firms in popularizing such codes. Focusing on the environmental policy arena, this article documents that such policy entrepreneurscorporate environmental entrepreneurs-exist in many corporations and signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…Alternatively, a non-significant effect represents a net zero impact of positive and negative externalities of governmental policies. The Saudi Arabian government may not be providing adequate instruments for green entrepreneurs to deal with existing risks and uncertainties, which will impair sustainable development [41,74]. Hence, our analysis may serve to derive theoretical and policy implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, a non-significant effect represents a net zero impact of positive and negative externalities of governmental policies. The Saudi Arabian government may not be providing adequate instruments for green entrepreneurs to deal with existing risks and uncertainties, which will impair sustainable development [41,74]. Hence, our analysis may serve to derive theoretical and policy implications.…”
Section: Discussionmentioning
confidence: 99%
“…To refocus domestic agendas on greener, more sustainable practices, governments also have the capacity to enforce and promote environmentally sound production methods [73] and to influence the policies shaping firm practices and investment objectives [74]. As incentivising measures, domestic entrepreneurship policies can leverage subsidies and target investment sectors in order to systemically increase the commitment to greener, more responsible enterprise [75].…”
Section: The Role Of Entrepreneurship Policy In Green Entrepreneurial Activity and Sustainable Developmentmentioning
confidence: 99%
“…The study by Raines and Prakash (2005), which relies on the statistical analysis of survey data, stands as an exception to the preponderance of qualitative analysis. Additionally, there are a few articles that use descriptive statistics extensively in a comparative fashion, such as Wampler (2009), Appel and Orenstein (2013), and Wetterberg and Brinkerhoff (2019).…”
Section: Methodsmentioning
confidence: 99%
“…We observed that the concept of "policy entrepreneurship" is not only used to understand and analyze public policy making. Of the 27 articles, two discuss policy entrepreneurs operating in corporations; Raines and Prakash (2005) The remaining 25 studies demonstrate diversity in many respects, even though they all look into changes in public policy or institutions.…”
Section: Units Of Analysis and Policy Areasmentioning
confidence: 99%
“…Although a program champion can be a technocratwithin or outside the government (Richard-Ferroudji, 2014)or a policy target who exhibits leadership in adopting the program (Raines & Prakash, 2005), she is more likely to be a mid-or low-level bureaucrat. Frontline-or street-level bureaucrats can play the role of a program champion by embedding a policy innovation into practice using "intellectual, social, and political capital" (Arnold, 2015).…”
Section: Program Championmentioning
confidence: 99%